PENENTUAN TEAM LEADER, SUPERVISOR DAN FACILITY SERVICES PADA PERUSAHAAN JASA BERDASARKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) - Merry Agustina (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Competition in the increasingly competitive business world spur companies to strive harder to improve the quality of their company. This research discusses the determination of Team Leader in a service company that provides integrated services that stood since the year 1996 with 9 branch offices up to now one of them in the city of Palembang. The services provided by the company are Integreted Facility Servises, Cleaning Services, Security Services, Property Services, Catering Services, Support Services, and Parking Services. In the determination of Team Leader, Supervisor and Facility Services there are 6 scoring criteria, namely Leadership, Communication Skills, Operational Forms, Operational Duties, Human Resources Aspects, and Motivational Session and Team Building. This research implemented SMART method in the process of determining Team Leader, Supervisor and Facility Services by using 12 employees proposed in February 2019, with the end of employees named Hartono elected as Team Leader With a value of 0.797. Employees named Jacop with a final value of 0.904 elected as Supervisor and employee named Dimas with final value 0, 789.